Peningkatan Kesadaran dan Kepatuhan terhadap Prinsip Sanitasi Makanan di Taman Kota Tarutung - Angelia Putriana; Siti Aisyah; Apriliani Lase; Sabam Syahputra; Aprilana Lase (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Increasing awareness and compliance with food sanitation principles is crucial for ensuring public safety and health. This study aims to evaluate and enhance awareness and adherence to food sanitation principles at Taman Kota Tarutung. Employing a quantitative approach, the research collects data through surveys and interviews with food vendors and visitors at the park. The primary focus is to identify the level of vendors' knowledge about food sanitation standards and to assess the implementation of proper sanitation practices in food preparation and storage. The results indicate that while most vendors have a basic understanding of food sanitation, compliance with good sanitation practices remains low. These findings highlight the need for more intensive educational programs and stricter enforcement of sanitation regulations. Recommendations include conducting food sanitation workshops, increasing routine inspections by local authorities, and launching awareness campaigns for visitors. This study is expected to contribute to improving food sanitation standards at Taman Kota Tarutung and enhancing overall public health